2011
DOI: 10.1007/s12160-011-9264-2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Motivation and Ongoing Exercise Activity in Cardiac Rehabilitation Settings: A 24-Month Exploration from the TEACH Study

Abstract: Identifying a patient's exercise and motivational profile could help cardiac rehabilitation programmes tailor their intervention to optimize the potential for continued exercise activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 38 publications
4
42
0
1
Order By: Relevance
“…Extending these findings, Sweet, Tulloch, Fortier, Pipe, and Reid (2011) demonstrated that self-determined individuals were more likely to maintain exercise behaviour up to 24 months following CR (N = 251, 79% male, M age = 61.4 years).…”
mentioning
confidence: 72%
“…Extending these findings, Sweet, Tulloch, Fortier, Pipe, and Reid (2011) demonstrated that self-determined individuals were more likely to maintain exercise behaviour up to 24 months following CR (N = 251, 79% male, M age = 61.4 years).…”
mentioning
confidence: 72%
“…According to self-determination theory, incentives may help to build self-determined motivation primarily through their action on self-efficacy, especially for lower active people who exhibit fewer intrinsic motives to begin with (less motivation to crowd out) [44,45]. Regarding physical activity, one hypothesis is that incentives may increase a person’s self-efficacy to become more active by exposing them to a form of physical activity for the first time [29,30,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding physical activity, one hypothesis is that incentives may increase a person’s self-efficacy to become more active by exposing them to a form of physical activity for the first time [29,30,44,45]. Especially if the activity is an achievable one (eg, walk 1000 more steps per day vs walk 10,000 steps per day), individuals may find their confidence to be more active increases after just a few weeks [29,30,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…If a person has a high sense of efficacy and positive outcome expectations, only minimal guidance is needed. People with self-doubt need more guidance and those with little feeling of control of lifestyle changes need the most structured programs to make healthy changes in life (Bandura 2004, see also Sweet et al 2011). By empowering methods the level of self-efficacy and the sense of control can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…In lifestyle changes different stages of change require different interventions (Ogden 2007, 21–22). Unrealistic expectations may lead to disappointment and a decrease in activity (Sweet et al 2011). …”
Section: Introductionmentioning
confidence: 99%